MENINGKATKAN KEMAMPUAN MEMAHAMI WACANA DENGAN MEMBACA MEMINDAI SISWA MELALUI PENDEKATAN INTEGRATIF - Manurung, Vanda (JURNAL GLOBAL EDUKASI, 2019)
Abstract: This research was conducted on students of class VIII of SMP Negeri 3 Muara Siatas Barita in the academic year 2017/2018 consisting of 24 students who aimed to find out: the ability to understand discourse by reading scanning students through an integrative approach in class VIII of SMP Negeri 3 Muara Siatas Barita academic year 2017/2018. Data collection instruments were carried out using tests of student learning outcomes, and observations. The data analysis technique in this class action research calculates the percentage of students completeness classically, and calculates the percentage of observations (observations) of the teacher and students. Based on the results of the study note that in the first cycle the average value of the class 57.69. For the percentage of classical completeness is 69.63%. In the second cycle, it is known that the average value of the class is 84.62. For the percentage of classical completeness is 100%. The results of teacher observation in the first cycle total score 29 with a percentage of 90.62%, and in the second cycle the total score of 32 with a percentage of 100%. So that the research was said to be successful in the second cycle because it had reached the KKM and the percentage of classical completeness with very high criteria. Keywords: discourse, scan reading, integrative Abstrak: Penelitan ini dilakukan pada siswa kelas VIII SMP Negeri 3 Muara Siatas Barita tahun pelajaran 2017/2018 yang terdiri dari 24 orang siswa yang bertujuan untuk mengetahui: kemampuan memahami wacana dengan membaca memindai siswa melalui pendekatan integratif di kelas VIII SMP Negeri 3 Muara Siatas Barita tahun pelajaran 2017/2018. Instrumen pengumpulan data dilakukan dengan menggunakan tes hasil belajar siswa, dan hasil pengamatan (observasi). Teknik analisis data pada penelitian tindakan kelas ini menghitung persentasi ketuntasan belajar siswa secara klasikal, dan menghitung persentasi hasil pengamatan (observasi) terhadap guru dan siswa. Berdasarkan hasil penelitian diketahui bahwa pada siklus I nilai rata-rata kelas 57,69. Untuk persentase ketuntasan klasikal adalah 69,63%. Pada siklus II diketahui nilai rata-rata kelas 84,62. Untuk persentase ketuntasan klasikal adalah 100%. Hasil observasi guru pada siklus I jumlah skor 29 dengan persentasi 90,62 %, dan pada siklus II jumlah skor 32 dengan persentasi 100%. Sehingga dengan demikian penelitian dikatakan berhasil pada siklus II karena telah mencapai KKM dan persentase ketuntasan klasikal dengan kriteria sangat tinggi. Kata kunci: wacana, membaca memindai, integratif